Epidemiological study of Cryptosporidiosis in sheep of Baghdad province: Alia Yousif Yakoob ;Thura Awad Kathim - Yakoob, Alia Yousif (The Iraqi Journal of Veterinary Medicine, 2009)
To investigate the prevalence of cryptosporidiosis among neonatal lambs and sheep in different areasof Baghdad include (Alshaab, Alshoala ,Albayaa, Alalawy, Madenat alsader, Aldorah, Alhosaenea,Algazalea, Alrashdea) ,also the study investigated effect of sex ,age, season on the infected rate fromDecember 2007 till August 2008.The laboratory methods were used to identified the oocysts :Modifide Ziehl Neelsen stain and flotationwith Shether’s solution .A total of 500 fecal samples were collected from animals at one day -two years old lambs and sheep,males and femalesAll fecal samples obtained from three groups of animals state: diarrhea , pasty and normal.The study recorded total rate of cryptosporidiosis infection 15.8% in neonatal lambs and sheep., thecryptosporidium oocysts isolated from animals appeared with Ziehl Neelsen stain as spherical ovalshape, red in color containing the sporozoit and measured 4.3 x 4.8 Um.Infected rate differ according to the areas, the higher rate of infection 34.88 % was recorded inAlshaab , while the lower rate 3.12 % was recorded in Algazalea.The result revealed higher rate of infection 34.95 % was recorded in lambs less than month , whilethe lower rate 2.77 % was recorded in animals at 6 to 7 month old.No significant difference was noticed between two sex , the infection rate was 12.9 % in males and16.75 % in females.The result revealed there’s no effect of fecal type on infection rate this study was recorded 18.61 %in diarrheic animals, 14.68 % in normal and 11.9 % in animals with pasty feces.In regard to seasonal variation, the higher rate of infection 34.88 % was recorded in April, while thelower rate 3.12 % in July.